2021
DOI: 10.1080/07481187.2021.1889722
|View full text |Cite
|
Sign up to set email alerts
|

The fear of the COVID-19 Scale: validation in the Portuguese general population

Abstract: The coronavirus disease (COVID-19) pandemic is having a profound effect on mental health and it is therefore fundamental to evaluate individual psychological responses to COVID-19. The 7-item Fear of COVID-19 Scale (FCV-19S) assesses different aspects of the fear of coronavirus and has been applied worldwide. This study aimed to translate and validate the FCV-19S in the Portuguese population. The scale was administered to a convenience sample of 1203 Portuguese adults. Exploratory factor analysis was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
2
13
0
1
Order By: Relevance
“…It had a positive relationship with perceived stress and negative relationship with wellbeing. These findings are also consistent with previous studies (Pakpour et al, 2020;Satici et al, 2020b;Soares et al, 2021). Thus the study provides a potential contribution to Fear of COVID literature by analyzing the psychometric properties of FCV-19S in India.…”
Section: Discussionsupporting
confidence: 91%
“…It had a positive relationship with perceived stress and negative relationship with wellbeing. These findings are also consistent with previous studies (Pakpour et al, 2020;Satici et al, 2020b;Soares et al, 2021). Thus the study provides a potential contribution to Fear of COVID literature by analyzing the psychometric properties of FCV-19S in India.…”
Section: Discussionsupporting
confidence: 91%
“…Since its development, the Fear of COVID-19 Scale has been translated and adapted to several languages [ 13 , 14 , 31 – 50 ]. The initial study examined the validity against the Hospital Anxiety and Depression Scale and Perceived Vulnerability to Disease Scale [ 30 ], similarly to the Portuguese [ 5 ], English [ 31 ], Italian [ 13 ], Arabic [ 46 ], Spanish [ 44 ] and Japanese [ 37 ] adaptations, while other studies confirmed the validity using various other measures of depression and anxiety [ 14 , 32 – 35 , 38 , 39 , 42 , 43 , 45 , 47 , 49 , 50 ]. The Fear of COVID-19 Scale has high reliability across translations and cultural adaptations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is debate whether the Fear of COVID-19 Scale has a stable single-factor structure [ 4 ] as reported in the initial study [ 30 ] and several adaptations [ 5 , 13 , 14 , 31 , 32 , 34 , 36 , 38 – 43 , 46 , 50 – 53 ] or if it is bi-factorial as reported in Paraguayan [ 44 ], Israeli [ 45 ], Chinese [ 47 ], Norwegian [ 49 ], Argentinian [ 33 ], Peruvian [ 35 ], Japanese [ 37 ] and Eastern European [ 54 ] populations. The two-factor models define a cognitive and somatic fear [ 49 ] or emotional and psychological [ 37 ] fear.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a study analysing the impact of the COVID-19 in Portugal, Brazil, and Colombia has uncovered vulnerabilities regarding poor sleep quality and mild to moderate suicidal ideation in the population of those countries [15]. Moreover, moderate levels of fear of the COVID-19 have been reported in the Portuguese population [17], and high levels of depressive symptoms, stress, and anxiety have also been evidenced among health professionals [18].…”
Section: Introductionmentioning
confidence: 99%